Clinical Efficacy of Nano Filled Resin Modified Glass Ionomer Cements in The Treatment of Class-V Non-Carious Cervical Lesion (Update Dental College Journal, 2026)
Introduction: With the expectation of having better clinical outcome in the treatment of class v non-carious cervical lesions, nano filled resin modified glass ionomer cement (RMGIC) has been introduced in dentistry. This study aimed to evaluate the clinical performance of nano filled RMGIC in the management of class V non-carious cervical lesions.Materials and methods: It was a randomized clinical trial carried out at the Department of Conservative Dentistry and Endodontics, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The patients had at least two non-carious cervical lesions on the buccal surface with approximal depth of 1-1.5 mm. Total 50 samples were included. Nano filled resin modified glass ionomer restoration was assessed by Modified Ryge’s Criteria by means of retention, color matching, marginal integrity and surface texture. Patients were recalled after 3, 6, and 12 months for follow up observation.  Results: At 12 months follow up, the retention of 47(94%) nano filled RMGIC showed Alpha rating.  Regarding color matching, nano filled RMGIC were more color stable observed. The marginal integrity of nano filled RMGIC was also better after six months interval. Further more polished enamel surface texture was achieved in 45 (90%) nano filled RMGIC at 12 months observation.Conclusion: The outcomes of using nano filled RMGIC in the restoration of cervical defects of teeth, prior to root coverage measures, were very encouraging regarding both clinical and patient-centered parameters such as retention, surface finish, and marginal integrity. For better understanding of the material, long term follow-ups are necessary.Update Dent. Coll. j: 2025; 15(2): 7-12